Global Trade and the Dollar - Boz, Emine (IMF Working Papers; Working Paper ;, 2017)
We document that the U.S. dollar exchange rate drives global trade prices and volumes. Using a newly constructed data set of bilateral price and volume indices for more than 2,500 country pairs, we establish the following facts: 1) The dollar exchange rate quantitatively dominates the bilateral exchange rate in price pass-through and trade elasticity regressions. U.S. monetary policy induced dollar fluctuations have high pass-through into bilateral import prices. 2) Bilateral non-commodities terms of trade are essentially uncorrelated with bilateral exchange rates. 3) The strength of the U.S. dollar is a key predictor of rest-of-world aggregate trade volume and consumer/producer price inflation. A 1 percent U.S. dollar appreciation against all other currencies in the world predicts a 0.6-0.8 percent decline within a year in the volume of total trade between countries in the rest of the world, controlling for the global business cycle. 4) Using a novel Bayesian semiparametric hierarchical panel data model, we estimate that the importing country's share of imports invoiced in dollars explains 15 percent of the variance of dollar pass-through/elasticity across country pairs. Our findings strongly support the dominant currency paradigm as opposed to the traditional Mundell-Fleming pricing paradigms.